Pathogenicity of entomopathogenic fungus Metarhizium spp. against predators Menochilus sexmaculatus Fabricius (Coleoptera: Coccinellidae) - TRIZELIA, TRIZELIA; BUSNIAH, MUNZIR; PERMADI, AGUNG (Asian Journal of Agriculture, 2017)
Trizelia, Busniah M, Agung Permadi A. 2017. Pathogenicity of entomopathogenic fungus Metarhizium spp. against predators Menochilus sexmaculatus Fabricius (Coleoptera: Coccinellidae). Asian J Agric 1: 1-5. Metarhizium spp is an entomopathogenic fungus which has wide host range. Metarhizium spp can not only infect insect pests, but can also infect beneficial insects such as predators. The pathogenicity of four isolates of Metarhizium spp. was investigated against Menochilus sexmaculatus predator. Isolates of Metarhizium spp were isolated from rhizosphere of cacao, cabbage, chili, and rubber crops. The experiment was conducted by treating the fourth instar larvae with an appropriate conidial suspension of 108 conidia mL-1. The results showed that all isolates of Metarhizium spp were pathogenic toward beetle predator M. sexmaculatus. Mortality of larvae within seven days after application of conidial suspension varied between 27.50 to 67.50% and there were statistically significant differences among the tested isolates. Metarhizium spp. had also a significant affect in reducing pupation and adult emergence of M. sexmaculatus to below 30% and 3%, respectively. These studies indicate that entomopathogenic fungus Metarhizium spp was pathogenic to beetle predators, M. sexmaculatus.